SOCIAL ANXIETY AS A BARRIER TO ADAPTATION TO HIGHER EDUCATION - Estrada, Zulma Sánchez; Zenteno, Jorge Noriega; Vazquez, Elizabeth Sánchez; Jara, Diego García; Alpizar, Diana Huitrón (Seven Editora, 2025)
Late adolescence constitutes a critical stage in the transition to higher education, characterized by academic, social, and emotional demands that may increase students’ psychological vulnerability. In this context, social anxiety represents one of the most frequent problems, as it directly interferes with academic participation, interpersonal interaction, and emotional well-being. This article aims to analyze a psychopedagogical case study of an 18-year-old university student identified with symptoms compatible with social anxiety and avoidant traits, based on an institutional support process. A qualitative methodology with a case study design was employed, supported by analysis of the psychopedagogical record, clinical observation, and longitudinal follow-up across several intervention sessions. The analysis of the records allowed the identification of initial manifestations of social inhibition, anticipatory fear of external judgment, intense self-criticism, cognitive rumination, and maladaptive emotional regulation strategies, such as self-external dialogue. Difficulties in the perception of family support and in interpersonal self-efficacy were also observed, which intensified during the university adaptation process. The psychopedagogical intervention was structured through strategies of gradual social exposure, cognitive restructuring, social skills training, work on self-perception and body image, and the strengthening of emotional containment skills. The results demonstrate a progressive evolution of the student, reflected in increased social initiative, reduced avoidant behaviors, a decrease in the frequency of self-external dialogue, and greater integration into academic and family contexts. It is concluded that age acts as a relevant triggering factor in the onset and maintenance of social anxiety during entry into university. Furthermore, the effectiveness of early psychopedagogical intervention is highlighted as a secondary prevention strategy, as it promotes emotional regulation, adaptation to the university environment, and academic persistence, consolidating the role of the educational institution as an active agent of comprehensive support in student mental health. DOI: https://doi.org/10.56238/sevened2025.038-082